Treatment of Infected Nonunions With Bone Defects Using Autologous Bone Graft and Absorbable Antibiotic-Loaded Calcium Sulfate–Hydroxyapatite Paste. (August 2022) - Howard, Theodore; Reichert, Ines; Giddie, Jasdeep; Ahluwalia, Raju
Background: Revision surgery in the presence of infection carries high risks. We describe our results using a new technique to treat these challenging problems. We treated infected nonunions with cavitary voids with adjuvant antibiotic loaded calcium sulfate–hydroxyapatite paste composite and autologous bone graft (ABG) layer technique coupled with stable fixation. Methods: Thirty consecutive patients who underwent revision foot and ankle surgery for an infected nonunion were prospectively studied. Following multidisciplinary team workup, surgical debridement and biopsies were undertaken. Bone voids were measured and classified according to containment and size. ABG was mixed and layered with an adjuvant antibiotic-loaded calcium sulfate–hydroxyapatite paste followed by surgical reconstruction including arthrodesis and fixation. Empirical and pathogen-specific antibiotics were instituted until intraoperative sample-specific antibiotics were identified and used. Patients were prospectively followed up for a minimum of 1 year. Results: The male-female ratio was 16:14, mean age was 51.3 years, and 23.3% smoked at definitive surgery. Void volume was <1 cm 3 (n=9), 1-2 cm 3 (n = 13), and >2 cm 3 (n=8). No patients either were lost to follow-up or had a further infective episode at a mean of 38.3 months; 86.7% united with fusion on imaging. Four patients had radiographic evidence of nonunion; 3 were asymptomatic and 1 required revision surgery (void >2 cm 3 ). Independent ambulation was achieved at an average of 12 weeks, at 1 year mean American Orthopaedic Foot & Ankle Society score was 77.7 (SD 9.59), and the Manchester-Oxford Foot Questionnaire reached an effect size >0.5 in all domains at 1 year following surgery. The union rate was independent of smoking status and vitamin D deficiency ( P = .94). Conclusion: Layered autologous bone grafting with adjuvant antibiotic-loaded calcium sulfate–hydroxyapatite paste has been shown to be effective and safe in revision arthrodesis, with low comorbidities in void gaps without infection recurrence.